A critical review of plant protection tools for reducing pesticide use on grapevine and new perspectives for the implementation of IPM in viticulture. (July 2017) - Pertot, I.; Caffi, T.; Rossi, V.; Mugnai, L.; Hoffmann, C.; Grando, M.S.; Gary, C.; Lafond, D.; Duso, C.; Thiery, D.; Mazzoni, V.; Anfora, G.
Abstract: Several pests and diseases have grapevine as their favourite host and the vineyard as preferred environment, so an intensive pesticide schedule is usually required to meet qualitative and quantitative production standards. The need to prevent the negative impact of synthetic chemical pesticides on human health and the environment and the consumer expectations in term of chemical residues in food stimulated the research of innovative tools and methods for sustainable pest management. The research project PURE (www.pure-ipm.eu ) was a Europe-wide framework, which demonstrated that several solutions are now available for the growers and evaluated several new alternatives that are under development or almost ready for being applied in practice. Although the use of resistant/tolerant varieties is not yet feasible in several traditional grape growing areas, at least part of the synthetic chemical pesticides can be substituted with biocontrol agents to control pests and pathogens and/or pheromone mating disruption, or the number of treatments can be reduced by the use of decision support systems, which identify the optimal timing for the applications. This review presents the state of the art and the perspectives in the field of grapevine protection tools and strategies. Highlights: Several pests and diseases affect the grapevine. IPM is mandatory to reduce pesticide risk. A review on the state of the art and the perspectives on pest protection tools and strategies.